The Impact of Technological and Marketing Innovations on Retailing Industry: Evidence of India - Khaled, Amgad S.D.; Ahmed, Salma; Tabash, Mosab I.; Al-Homaidi, Eissa A.; Hossain, Mohammad Imtiaz (Journal of Reviews on Global Economics, 2019)
Innovation is usually linked with technology-based change. Retailers form a significant sector in the developed economies and also are picking up in the developing economies. There have been few studies in the area of innovation in the retail industry in both conceptual as well as empirical points of view. The objective of this study is to study the impact of marketing and technological innovations on the retail industry. The sample of the study was drawn from the customers who live in the city of Aligarh in India. The study is conclusive, descriptive and is based on a single cross-sectional research design. Quantitative data was generated on the basis of the research instrument (a questionnaire). The study concluded that technological innovation is more important than marketing innovation with respect to World of Mouth (WOM) referral and satisfaction. Furthermore, the study revealed that technological innovation has an impact on store image, customer value, brand store equity, satisfaction, WOM referral, and WOM activity. The study also recommended that a retailer can take some advantages of introducing new technologies. This means investing in technologies would help in increasing market share and competitiveness of the retail sector in the long-run.